1965
DOI: 10.1139/v65-345
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectra of Some Furoquinoline Alkaloids

Abstract: The mass spectra of six furoquinoline alkaloids have been recorded and mechanisms have been proposed for their fragmentation upon electron impact. Strong metastable peaks, present in all spectra, have aided in the interpretation of the fragmentation of these alkaloids. The three alkaloids with a methoxyl group in the 8-position of the quinoline ring may be differentiated from the other three by the presence of relatively intense peaks a t M-1 and M-29.In this investigation we wish to report upon the fragmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
5

Year Published

1970
1970
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 3 publications
2
9
0
5
Order By: Relevance
“…Histological studies of pigs inoculated with EDP [15] (herein designated SLT-II variant) and mice or rabbits inoculated with Shiga toxin [16,17] suggest that these toxins may cause vascular lesions in animals. Furthermore, it has been postulated that the neurological signs observed in pigs with ED and mice or rabbits inoculated with Shiga toxin are secondary effects of alterations in the vasculature of the central nervous system rather than the result of the direct action of EDP or Shiga toxin on nerve cells [5,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies of pigs inoculated with EDP [15] (herein designated SLT-II variant) and mice or rabbits inoculated with Shiga toxin [16,17] suggest that these toxins may cause vascular lesions in animals. Furthermore, it has been postulated that the neurological signs observed in pigs with ED and mice or rabbits inoculated with Shiga toxin are secondary effects of alterations in the vasculature of the central nervous system rather than the result of the direct action of EDP or Shiga toxin on nerve cells [5,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…lycopersici (tomato) [5]. A number of coumarins, e. g. isogospherol (2) [6], heraclenol (3) [7], (+)-7-methoxy-6-(2 R-methoxy-3 -hydroxy-3 -methyl butyl)coumarin (4) [1], 5,8-dimethoxy coumarin-2H-1-benzopyran-2-one (5) [8], 7-methoxy-6-[2 -oxo-3 -methyl butyl]coumarin (6) [9] and (+)-ulopterol (7) [10,11], were isolated, in addition to various quinoline alkaloids, e. g. 4-methoxy-1-methyl-3-(2 S-acetoxy-3 -ene butyl)-2-quinolone (8) [12], 4-methoxy-1-methyl-3-(2 S-acetoxy-3 -hydroxy butyl)-2-quinolone (9) [12], 3-hydroxy-2,2,6-trimethyl-3,4,5,6-tetrahydro-2H-pyrano[3,2-c]quinoline-5-one (10) [13], 4-methoxy-1-methyl-3-(2 -oxo-3 -methyl butyl)-2-quinolone (11) [15], 4-methoxy-1-methyl-3-(2 S-hydroxy-3 -ene butyl)-2-quinolone (12) [12], methyl isoplatydesmine (13) [2], ribalinin (14) [14] and dictamnine (15) [15 -18].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that SLT-I and SLT-II of E. coli O157 : H7 strains are not active in piglets: they were not able to induce fluid transudation nor did they cause mucosal lesions [20]. In contrast lesions were demonstrated with SLT-IIp [21]. 2.…”
Section: Discussionmentioning
confidence: 99%